Children, youth and adults with Asperger Syndrome : integrating multiple perspectives - Stoddart, Kevin P., 1962- (Jessica Kingsley Publishers, 2005)
This book offers a comprehensive overview of clinical, research and personal perspectives on Asperger Syndrome, including contributions from parents and experts in the fields of psychology, social work, psychiatry, genetics, sexology and vocational counselling.